2014
DOI: 10.1098/rspb.2014.0480
|View full text |Cite
|
Sign up to set email alerts
|

Zebra finches are sensitive to prosodic features of human speech

Abstract: Variation in pitch, amplitude and rhythm adds crucial paralinguistic information to human speech. Such prosodic cues can reveal information about the meaning or emphasis of a sentence or the emotional state of the speaker. To examine the hypothesis that sensitivity to prosodic cues is language independent and not human specific, we tested prosody perception in a controlled experiment with zebra finches. Using a go/no-go procedure, subjects were trained to discriminate between speech syllables arranged in XYXY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…While earlier studies using a go/no go procedure have demonstrated that zebra finches are able to discriminate artificial stimuli differing in number, sequence, intensity or frequency profile of vocal elements (e.g., Lohr and Dooling, 1998;Spierings and ten Cate, 2014;Verzijden et al, 2007;Weisman et al, 1998), it so far has not been examined whether they can discriminate stimuli in which the relative timing of otherwise identical elements has been varied. Therefore, in our first experiment, we trained the birds to distinguish between one isochronous and one irregular stimulus.…”
Section: Experiments 1: Single Training Stimulimentioning
confidence: 99%
“…While earlier studies using a go/no go procedure have demonstrated that zebra finches are able to discriminate artificial stimuli differing in number, sequence, intensity or frequency profile of vocal elements (e.g., Lohr and Dooling, 1998;Spierings and ten Cate, 2014;Verzijden et al, 2007;Weisman et al, 1998), it so far has not been examined whether they can discriminate stimuli in which the relative timing of otherwise identical elements has been varied. Therefore, in our first experiment, we trained the birds to distinguish between one isochronous and one irregular stimulus.…”
Section: Experiments 1: Single Training Stimulimentioning
confidence: 99%
“…The low number of responses to the stimuli with new items in test 6 might reflect a weakness of the test procedure of the go/no-go task that has been noted before (9,15,16,40). Because only the go training stimuli (consisting of familiar items) provided a reward, the budgerigars might quickly have learned to ignore any stimulus containing novel items.…”
mentioning
confidence: 99%
“…Further comparative research on temporal structure perception in speech with nonhuman animal species could better inform our understanding of the evolutionary path of such an ability, determining how much this ability depends on general pattern learning processes vs. speech-specific combination of cues (Ramus et al, 2000; Toro et al, 2003; Patel, 2006; Fitch, 2012; de la Mora et al, 2013; Ravignani et al, 2014; Spierings and ten Cate, 2014; Hoeschele and Fitch, 2016). …”
Section: General Discussion and Conclusionmentioning
confidence: 99%